Collation shrink film
By using a single-layer or multi-layer film structure containing the formulated resin, the unevenness and contamination problems of the recovery of HDPE resin in the finishing shrink film are solved, and the good mechanical characteristics and shrinkage properties of the film are achieved.
Patent Information
- Application Number
- CN202180043026.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-11
- Filing Date
- 2021-05-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-05-10
AI Technical Summary
The finishing shrink film prepared using recycled high-density polyethylene resin (HDPE) in the prior art has problems such as resin unevenness, high pollution and defects in the film, such as gel formation, reduced processability and deterioration of mechanical properties.
A single-layer or multi-layer film structure containing a formulation resin consisting of a post-consumer recovery resin derived from recycled HDPE and low-density polyethylene (LDPE) or linear low-density polyethylene (LLDPE) to ensure the mechanical properties and shrinkage properties of the film.
The finishing shrink film prepared using recycled materials has good mechanical properties and shrinkage properties, while avoiding the problems of resin unevenness and high pollution, ensuring the quality and reliability of the film.
Smart Images

Figure BDA0004001978450000131 
Figure BDA0004001978450000132 
Figure BDA0004001978450000141
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure relate generally to packaging films; and more particularly, to collation shrink films and the preparation of such films. Background Art
[0002] Using recycled materials is considered better for the environment and reduces the waste of natural resources used for disposable products. Typically, the largest source of recycled materials is the plastic packaging industry (e.g., plastics used to make containers such as milk jugs, plastic bags, and refillable plastic bottles). It is advantageous for the plastics industry to develop methods for recovering plastic materials that would otherwise become waste by being incinerated or placed in landfills. However, using recycled materials has disadvantages. It is generally recognized in the art that recycled materials often result in products whose physical properties are generally not as acceptable as those of products made from virgin materials. Therefore, the amount of recycled materials used in a product is often limited due to the loss of physical properties of products made from recycled materials.
[0003] One end-use application for which there is an increasing demand for recycled materials is collation shrink packaging. The process of shrink packaging generally involves wrapping an article or item in a heat-shrinkable collation shrink film (CSF) to form a package, and then heat shrinking the film by exposing the film to sufficient heat to cause shrinkage of the film and intimate contact between the film and the article. Collation shrink films (also known as "shrink wrap films," "heat shrink films," or "shrink films") are required to possess, among other properties, (1) good shrinkage and sufficient stiffness to allow the film to properly wrap the packaged item; (2) sufficient dimensional shrinkage to ensure a snug fit; and (3) a sufficiently low coefficient of friction (COF). For example, a film suitable for use as a collation shrink film must have high heat shrink force to ensure a snug fit and high tensile strength to withstand handling and abuse during shipping, and have excellent optical properties, such as low haze and high gloss, as well as good clarity. This is typically accomplished using low-density polyethylene (LDPE) and / or linear low-density polyethylene (LLDPE) because LDPE and LLDPE have good shrink properties.
[0004] High-density polyethylene (HDPE) is a plastic with high potential for use as PCR because HDPE is easily recycled; and HDPE is a good source of PCR because HDPE is one of the most commonly used plastics in the manufacture of containers (such as milk jugs, plastic bags, and refillable plastic bottles). In addition, almost all HDPE containers are made from the same grade of resin (fractional melt index homopolymer); and the use of recycled HDPE produces a uniform feed stream with consistent material properties that are evident in predictable performance properties and flow (processing) characteristics. In fact, recycled HDPE has been used as PCR to make plastic wood (lumber), recycled plastic furniture, lawn and garden products, buckets, crates, office products, and automotive parts. However, the use of PCR to make collation shrink films is limited due to the following reasons: (1) the lack of uniformity of PCR resins; (2) the high contamination of PCR resins, and (3) the presence of defects in films produced using PCR (e.g., undesirable gel formation, reduced processability, and deterioration of the mechanical properties of the film). Therefore, there is a need to find solutions to the above-mentioned defect problems in films when using recycled products to produce films or other articles, without affecting the quality of the films or other articles.
[0005] One reference that discloses the use of HDPE and LDPE includes U.S. Pat. No. 7,422,786, which discloses a 3-layer shrink film having: a core layer comprising a combination of HDPE and LDPE; and a skin layer comprising metallocene polyethylene (mPE) or LLDPE to provide a film structure with beneficial properties (such as good stiffness, high clarity and / or excellent shrink performance).
[0006] Other collation shrink films made from various polymer blends are known in the art and are described, for example, in EP1941998A1, EP2875948A1, WO2012 / 164308A1, WO2013 / 081742A1, US Patent Application Publication Nos. 2002 / 0187360 and 2005 / 0064161A1, and US Patent Nos. 6,187,397, 6,340,532, 6,368,545, and 6,824,886.
[0007] None of the above prior art references are believed to provide a CSF film product that is made from a clean stream of post-consumer resin (PCR) HDPE having a certain melt index (MI) and density; and is a fully recyclable mono-material PE structure. Furthermore, none of these prior art references are believed to disclose a PCR polymer blend composition for making a CSF film product for a 3-layer film structure having the above PCR blend in the core layer and two skin layers on each side surface of the PCR blend core layer. Summary of the invention
[0008] In embodiments herein, a shrink film is disclosed. The shrink film comprises a monolayer or multilayer film having at least one layer comprising a formulated resin; wherein the formulated resin comprises: a post-consumer recycled resin derived from a recycled high-density polyethylene resin; wherein the post-consumer recycled resin has a density of 0.94 g / cc to 0.97 g / cc, a melt index I2 of 0.2 g / 10 min to 1 g / 10 min, and (i) a low density polyethylene (LDPE), wherein the LDPE has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; or (ii) a linear low density polyethylene (LLDPE), wherein the LLDPE has a density of 0.915 g / cc to 0.945 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; or (iii) a combination of (i) and (ii).
[0009] Also disclosed herein is a method for making the shrink film. The method includes providing a formulated resin, and forming a monolayer or multilayer film from the formulated resin. The formulated resin comprises: a post-consumer recycled resin derived from recycled high-density polyethylene resin; wherein the post-consumer recycled resin has a density of 0.94 g / cc to 0.97 g / cc, a melt index I2 of 0.2 g / 10 min to 1 g / 10 min, and (i) a low-density polyethylene (LDPE), wherein the LDPE has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; or (ii) a linear low-density polyethylene (LLDPE), wherein the LLDPE has a density of 0.915 g / cc to 0.945 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; or (iii) a combination of (i) and (ii).
[0010] Also disclosed herein is a multilayer shrink film. The multilayer shrink film comprises a core layer and two skin layers, wherein the skin layers comprise high optical skin layers, and wherein the core layer comprises a formulated resin. The formulated resin comprises: a post-consumer recycled resin derived from a recycled high-density polyethylene resin; wherein the post-consumer recycled resin has a density of 0.94 g / cc to 0.97 g / cc, a melt index I2 of 0.2 g / 10 min to 1 g / 10 min, and (i) a low-density polyethylene (LDPE), wherein the LDPE has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; or (ii) a linear low-density polyethylene (LLDPE), wherein the LLDPE has a density of 0.915 g / cc to 0.945 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; or (iii) a combination of (i) and (ii).
[0011] Further disclosed herein is an article packaged using the single-layer or multi-layer shrink film as described herein. DETAILED DESCRIPTION
[0012] Reference will now be made in detail to embodiments of shrink films containing PCR materials. The films may be used in finishing shrink applications; however, it should be noted that this is merely an exemplary illustrative implementation of the embodiments disclosed herein. The embodiments are suitable for other technologies that wish to incorporate PCR materials; have a low number of defects; exhibit good mechanical properties; and exhibit good shrink properties.
[0013] As used herein, the term "polyethylene" or "ethylene-based polymer" shall mean a polymer comprising greater than 50 mole % of units derived from ethylene monomers. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE); linear low density polyethylene (LLDPE); medium density polyethylene (MDPE); and high density polyethylene (HDPE).
[0014] The term "LDPE" may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene", and is defined to mean a polymer that is partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator such as a peroxide (see, e.g., U.S. Pat. No. 4,599,392). LDPE resins typically have a density in the range of 0.915 g / cm to 0.935 g / cm.
[0015] The term "LLDPE" includes resins made using a Ziegler-Natta catalyst system, as well as resins made using single-site catalysts, including but not limited to dual metallocene catalysts (sometimes referred to as "m-LLDPE") and constrained geometry catalysts; and resins made using post-metallocene and molecular catalysts. LLDPE comprises linear, substantially linear or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE, and includes substantially linear ethylene polymers (which are further defined in U.S. Pat. Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155), homogeneously branched linear ethylene polymer compositions (such as those in U.S. Pat. No. 3,645,992), heterogeneously branched ethylene polymers (such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698), and / or blends thereof (such as those disclosed in U.S. Pat. Nos. 3,914,342 or 5,854,045). LLDPE resins can be prepared via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0016] The term "MDPE" refers to polyethylene having a density of 0.926 g / cc to 0.945 g / cc. "MDPE" is typically prepared using chromium or Ziegler-Natta catalysts or using single site catalysts including but not limited to dual metallocene catalysts and constrained geometry catalysts.
[0017] The term "HDPE" refers to polyethylene having a density greater than 0.945 g / cc, which is typically produced using Ziegler-Natta catalysts, chromium catalysts, or single-site catalysts including but not limited to dual metallocene catalysts and constrained geometry catalysts.
[0018] ISO 14021:2016 defines “post-consumer recycled (PCR) material” as material that is generated by the end user of a product, either in households or in commercial, industrial and institutional facilities in the function of such facilities and that can no longer be used for the product’s intended purpose. PCR material includes material returned from the distribution chain.
[0019] As used throughout this specification, unless the context clearly indicates otherwise, the abbreviations given below have the following meanings: "=" means "equal to"; "@" means "at"; "<" means "less than"; ">" means "greater than"; "I2" refers to the "melt index" measured at 2.16 kg and 190°C; g = gram; mg = milligram; pts = parts by weight; kg = kilogram; kg / h = kilogram per hour; g / cc = gram per cubic centimeter; kg / m 3= kilogram per cubic meter; g / mol = grams per mole; L = liter; mL = milliliters; g / L = grams per liter; Mw = weight average molecular weight; Mn = number average molecular weight; Mz = z average molecular weight; m = meter; μm = micrometer; mm = millimeter; cm = centimeter; min = minute; s = second; mm / s2 = millimeter per square second; mm / s = millimeter per second; ms = millisecond; hr = hour; mm / min = millimeter per minute; m / s = meter per second; ℃ = degrees Celsius; ℃ / min = degrees Celsius per minute; mPa.s = millipascal-second; MPa = megapascal; kPa = kilopascal; Pa.s / m 2 = Pascal-second (s) per square meter; N = Newton; cN = hundredth of a Newton; rpm = revolutions per minute; mm 2 = square millimeters; g / 10min = grams per 10 minutes; J = joule; J / g = joule per gram; % = percent; eq% = equivalent percent; vol% = volume percent; and wt% = weight percent.
[0020] Unless otherwise indicated, all percentages, parts, ratios and similar amounts are defined by weight. For example, unless otherwise indicated, all percentages described herein are weight percentages (wt %).
[0021] Unless otherwise specified, temperatures are expressed in degrees Celsius (°C), and "ambient temperature" means between 20°C and 25°C.
[0022] In one or more embodiments, the present invention relates to a shrink film having at least one layer comprising a formulated resin. In embodiments herein, the at least one layer may comprise at least 50 wt.%, at least 75 wt.%, at least 80 wt.%, at least 85 wt.%, at least 90 wt.%, at least 95 wt.%, at least 97 wt.%, at least 99 wt.%, or 100 wt.% of a formulated resin. The shrink film may be a fully recyclable single material PE structure without any barrier layer added to the film PE product structure.
[0023] As previously described herein, the formulated resin comprises a post-consumer recycled resin derived from recycled high density polyethylene resin, and (i) a low density polyethylene (LDPE), or (ii) a linear low density polyethylene (LLDPE), or (iii) a combination of (i) and (ii). In one or more embodiments herein, the formulated resin comprises 20 wt % to 100 wt % (alternatively, a lower limit of 30 wt %, 35 wt %, 40 wt %, 50 wt % or 60 wt % to an upper limit of 100 wt %, 90 wt %, 80 wt % or 75 wt %) of post-consumer recycled resin. In some embodiments, the formulated resin comprises 30 wt % to 100 wt %, 35 wt % to 100 wt %, 35 wt % to 90 wt % or 40 wt % to 80 wt % of post-consumer recycled resin. In addition to the amount of post-consumer recycled resin in the formulated resin, in one or more embodiments herein, the formulated resin concentration of component (i) is 0 wt % to 60 wt %, or alternatively 5 wt % to 60 wt %, 5 wt % to 50 wt %, 5 wt % to 40 wt %, 5 wt % to 30 wt %, or 10 wt % to 30 wt %. In addition to the amount of post-consumer recycled resin and component (i) in the formulated resin, in one or more embodiments herein, the formulated resin concentration of component (ii) is 0 wt % to 60 wt %, or alternatively 10 wt % to 60 wt %, 25 wt % to 60 wt %, 30 wt % to 60 wt %, 30 wt % to 50 wt %, or 35 wt % to 50 wt %. In some embodiments, the formulated resin comprises PCR and LDPE in the amounts previously mentioned. In other embodiments, the formulated resin comprises PCR and LLDPE in the amounts previously mentioned. In further embodiments, the formulated resin comprises PCR, LDPE, and LLDPE in the amounts previously mentioned.
[0024] The post-consumer recycled resin is derived from recycled high density polyethylene resin. The post-consumer recycled resin has a density of 0.94 g / cc to 0.97 g / cc, a melt index I2 of 0.2 g / 10 min to 1 g / 10 min. All individual values and subranges are included and disclosed herein. For example, in some embodiments, the post-consumer recycled resin has a density of 0.94 g / cc to 0.97 g / cc (alternatively, 0.940 g / cc to 0.970 g / cc, 0.945 g / cc to 0.970 g / cc, 0.945 g / cc to 0.965 g / cc, or 0.945 g / cc to 0.960 g / cc) and a melt index I2 of 0.2 g / 10 min to 1 g / 10 min (alternatively, 0.2 g / 10 min to 1.0 g / 10 min, 0.2 g / 10 min to 0.8 g / 10 min, 0.2 g / 10 min to 0.6 g / 10 min, 0.2 g / 10 min to 0.5 g / 10 min, or 0.2 g / 10 min to 0.4 g / 10 min).
[0025] Generally speaking, PCR resins can be derived from packaging waste, such as materials generated by households or commercial, industrial and institutional facilities in their role as end users of products. It is an object of the present invention to provide a formulated PCR solution for shrink film, wherein a clean PCR feed stream is used in the shrink film. In one or more embodiments, the post-consumer recycled resin is derived from HDPE plastic containers. In one or more embodiments, the post-consumer recycled resin is derived from HDPE blow molded bottles (e.g., baby bottles, spice bottles, etc.). In one embodiment, the HDPE blow molded bottle has a melt index I2 of 0.30 g / 10 min±0.20 g / 10 min and a melt index I2 of 0.95 g / cm 3 ±0.02g / cm 3 density.
[0026] In embodiments herein, the LDPE has a density from 0.915 g / cc to 0.925 g / cc and a melt index I2 from 0.1 g / 10 min to 1 g / 10 min. All individual values and subranges are included and disclosed herein. For example, in some embodiments, the LDPE has a density of 0.915 g / cc to 0.925 g / cc (alternatively, 0.917 g / cc to 0.925 g / cc, 0.919 g / cc to 0.925 g / cc, or 0.919 g / cc to 0.923 g / cc) and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min (alternatively, 0.1 g / 10 min to 1.0 g / 10 min, 0.1 g / 10 min to 0.8 g / 10 min, 0.1 g / 10 min to 0.6 g / 10 min, 0.1 g / 10 min to 0.5 g / 10 min, or 0.1 g / 10 min to 0.4 g / 10 min).
[0027] Examples of suitable LDPE may include commercially available resins such as LDPE 150E available from The Dow Chemical Company or LDPE 310E available from The Dow Chemical Company.
[0028] In embodiments herein, the LLDPE has a density from 0.915 g / cc to 0.945 g / cc and a melt index I2 from 0.1 g / 10 min to 1 g / 10 min. All individual values and subranges are included and disclosed herein. For example, in some embodiments, the LLDPE has a density of 0.915 g / cc to 0.945 g / cc (alternatively, 0.915 g / cc to 0.940 g / cc, 0.915 g / cc to 0.938 g / cc, or 0.917 g / cc to 0.938 g / cc) and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min (alternatively, 0.1 g / 10 min to 1.0 g / 10 min, 0.1 g / 10 min to 0.8 g / 10 min, 0.1 g / 10 min to 0.6 g / 10 min, 0.1 g / 10 min to 0.5 g / 10 min, or 0.1 g / 10 min to 0.4 g / 10 min).
[0029] Examples of suitable LLDPE may include commercially available compounds such as TUFLIN TM 、DOWLEX TM 、DOWLEX TM NG and ELITE TM Resins (all available from Dow Chemical Company) and mixtures thereof; ENABLE TMand EXCEED TM Resins (all available from ExxonMobil) and mixtures thereof; LUMICENE TM and SUPERTOUGH TM resins (all available from Total) and mixtures thereof; and blends of two or more of the above resins. Specific examples of suitable LLDPEs may include, for example, DOWLEX TM 2045G resin, DOWLEX TM 2049G resin, DOWLEX TM 2098P resin, DOWLEX TM 2038.68G resin, DOWLEX TM 2645G resin and DOWLEX TM NG 5045P resin (both available from Dow Chemical Company) and mixtures thereof.
[0030] In the embodiments described herein, the formulated resin may have a density of 0.925 g / cc to 0.960 g / cc. All individual values and subranges from at least 0.925 g / cc to 0.960 g / cc are included and disclosed herein. For example, in some embodiments, the formulated resin has a density of 0.925 g / cc to 0.960 g / cc. 3 Up to 0.955g / cm 3 , 0.930g / cm 3 Up to 0.955g / cm 3 , 0.935g / cm 3 Up to 0.955g / cm 3 or 0.935g / cm 3 Up to 0.950g / cm 3 Density. Density can be measured according to ASTM D792.
[0031] In addition to density, the formulated resin may have a molecular weight distribution (Mw / Mn) of 2.0 to 10.0. All individual values and subranges of 2.0 to 10.0 are included and disclosed herein. For example, in some embodiments, the formulated resin may have a Mw / Mn ratio of a lower limit of 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, or 6.0 to an upper limit of 10.0, 9.5, 9.0, 8.5, or 8.0. In other embodiments, the formulated resin may have a Mw / Mn ratio of 5.0 to 10.0. In another embodiment, the formulated resin may have a Mw / Mn ratio of 6.0 to 9.0. In another embodiment, the formulated resin may have a Mw / Mn ratio of 6.0 to 8.5. Molecular weight distribution can be described as a weight average molecular weight (Mw / Mn). w ) and number average molecular weight (Mn ) ratio (i.e., M w / M n ), and can be measured by gel permeation chromatography techniques.
[0032] In addition to density and molecular weight distribution, the formulated resin may have a melt index I2 of 0.1 g / 10 min to 1.0 g / 10 min. All individual values and subranges of 0.1 g / 10 min to 1.0 g / 10 min are included and disclosed herein. For example, in some embodiments, the polyethylene composition may have a melt index I2 of 0.1 g / 10 min to 0.8 g / 10 min, 0.1 g / 10 min to 0.6 g / 10 min, 0.1 g / 10 min to 0.5 g / 10 min, or 0.1 g / 10 min to 0.4 g / 10 min. Melt index I2 can be measured according to ASTM D1238 (190 ° C and 2.16 kg).
[0033] In addition to density, molecular weight distribution and melt index I2, the formulated resin may have a melt flow ratio I10 / I2 of 10.0 to 25.0. All individual values and subranges of 10.0 to 25.0 are included and disclosed herein. For example, in some embodiments, the formulated resin may have a melt flow ratio I10 / I2 of a lower limit of 10.0, 12.0 or 14.0 to an upper limit of 25.0, 23.0 or 22.0. In one or more embodiments, the formulated resin may have a melt flow ratio I10 / I2 of 12.0 to 25.0, 14.0 to 23.0 or 14.0 to 22.0. Melt index I10 can be measured according to ASTM D1238 (190°C and 10.0kg).
[0034] In addition to density, molecular weight distribution, melt index I2, and melt flow ratio I10 / I2, the formulated resin may have a melt flow ratio I21 / I2 from 25 to 200. All individual values and subranges from 25 to 200 are included and disclosed herein. For example, in some embodiments, the formulated resin may have a melt flow ratio I21 / I2 from a lower limit of 25, 30, 40, or 50 to an upper limit of 200, 175, 150, 125, 110, or 90. In one or more embodiments, the formulated resin may have a melt flow ratio I21 / I2 from 40 to 150, 40 to 125, or 50 to 110. The melt index I21 can be measured according to ASTM D1238 (190° C. and 21.6 kg).
[0035] In addition to density, molecular weight distribution, melt index I2, melt flow ratio I10 / I2 and I21 / I2, the formulated resin can have a number average molecular weight Mn (g / mol) of 10,000 g / mol to 50,000 g / mol. All individual values and subranges of 10,000 g / mol to 50,000 g / mol are included and disclosed herein. For example, the formulated resin can have an Mn of 12,000 g / mol to 50,000 g / mol, 12,000 g / mol to 45,000 g / mol, 12,000 g / mol to 30,000 g / mol, or 12,000 g / mol to 27,000 g / mol.
[0036] In addition to density, molecular weight distribution, melt index I2, melt flow ratio I10 / I2, I21 / I2, and number average molecular weight, the formulated resin may have a weight average molecular weight Mw (g / mol) of 80,000 g / mol to 200,000 g / mol. All individual values and subranges of 80,000 g / mol to 200,000 g / mol are included and disclosed herein. For example, the formulated resin may have an Mw of 95,000 g / mol to 185,000 g / mol, 100,000 g / mol to 175,000 g / mol, or 110,000 g / mol to 170,000 g / mol.
[0037] In addition to density, molecular weight distribution, melt index I2, melt flow ratio I10 / I2, I21 / I2, number average molecular weight and weight average molecular weight, the formulated resin can have a z-average molecular weight Mz (g / mol) of 300,000 g / mol to 1,000,000 g / mol. All individual values and subranges of 300,000 g / mol to 1,000,000 g / mol are included and disclosed herein. For example, the formulated resin can have an Mz of 350,000 g / mol to 950,000 g / mol, 400,000 g / mol to 900,000 g / mol, or 500,000 g / mol to 900,000 g / mol.
[0038] In addition to density, molecular weight distribution, melt index I2, melt flow ratio I10 / I2, I21 / I2, number average molecular weight, weight average molecular weight and z-average molecular weight, the formulated resin may have an Mz / Mw of 3 to 10. All individual values and subranges of 3 to 10 are included and disclosed herein. For example, in some embodiments, the formulated resin may have an Mz / Mw of a lower limit of 3, 3.0, 3.5 or 4.0 to an upper limit of 10, 10.0, 9.0, 8.5, 8.0, 7.5, 7.0 or 6.5. In other embodiments, the formulated resin may have an Mz / Mw ratio of 3.0 to 9.0, 3.0 to 8.0, 3.0 to 7.5 or 3.5 to 6.5. Mz can be measured by gel permeation chromatography.
[0039] In addition to density, molecular weight distribution, melt index I2, melt flow ratio I10 / I2, I21 / I2, number average molecular weight, weight average molecular weight, z average molecular weight, and Mz / Mw, the formulated resin can have a melt strength from 0.03N to 0.25N. All individual values and subranges from 0.03N to 0.25N are included and disclosed herein. For example, in some embodiments, the formulated resin can have a melt strength from 0.05N to 0.20N or from 0.06N to 0.17N.
[0040] In embodiments herein, the formulation resin may include one or more additives. The additives combined with the compositions of the present invention may be formulated to achieve the performance of a specific function while maintaining the excellent benefits / properties of the formulation resin. For example, the following additives may be blended with the formulation resin, including: antioxidants, pigments, colorants, UV stabilizers, UV absorbers, processing aids, fillers, slip agents, anti-caking agents, etc.; and mixtures thereof.
[0041] When used in a formulated resin, the optional additives may be present in an amount generally ranging from 0% to 10% by weight in one embodiment; in an amount ranging from about 0.001% to 5% by weight in another embodiment; and in an amount ranging from 0.001% to 3% by weight in yet another embodiment. In other embodiments, the optional additives may be added to the formulated resin in an amount less than 5% by weight in one general embodiment, less than 3% by weight in another embodiment, and less than 1% by weight in yet another embodiment.
[0042] The shrink film can be a monolayer film or a multilayer film. In one or more embodiments of the present invention, the multilayer film has at least one layer comprising a formulated resin. In other embodiments, the multilayer film has at least three layers, at least one of which comprises a formulated resin. In other embodiments, the multilayer film comprises a core layer and two skin layers, wherein one skin layer (of the two skin layers) is on each side of the core layer, and the core layer comprises a formulated resin. The core layer may comprise at least 50wt.%, at least 75wt.%, at least 80wt.%, at least 85wt.%, at least 90wt.%, at least 95wt.%, at least 97wt.%, at least 99wt.% or 100wt.% of a formulated resin.
[0043] The process for preparing the formulated resin includes, for example, mixing the above components (a), (b) and (c) and any desired optional additives together. Mixing can be achieved using a dry blending process or a melt blending process, both of which are well known to those skilled in the art of mixing. In some embodiments, the formulated resin is a melt blended formulated resin.
[0044] Some advantageous / beneficial properties exhibited by melt blend formulated resins may include, for example: formulated resins with less gel formation; and more uniform formulated resins. Without being bound by theory, it is believed that the melt blending process may break up the gels and reduce the gel size. It is also believed that the melt filtration system used in melt blending may also contribute to gel reduction. Melt blending has an additional mixing step that enables better mixing compared to dry blending processes.
[0045] In one or more embodiments, the shrink monolayer or multilayer film can have any desired length and width; and have a thickness of, for example, 30 microns to 120 microns. All individual values and subranges from 30 microns to 120 microns are included and disclosed herein. For example, in some embodiments, the shrink monolayer or multilayer film can have a thickness of 30 microns to 100 microns, 30 microns to 90 microns, or 30 microns to 80 microns.
[0046] Also disclosed herein is a method for making the shrink film. The method includes providing a formulated resin as described in one or more embodiments of the present invention, and forming a monolayer or multilayer film from the formulated resin. Any conventional film forming process can be used to form the monolayer or multilayer film. An example includes a blown film production line (e.g., a blow molding line manufactured by Battenfeld Gloucester) using typical manufacturing parameters that are easily determined by a technician in the field of producing blown films.
[0047] In some embodiments, the shrink film can be a multilayer shrink film having the following film structure: an A / B / A film structure, wherein each A is a skin layer of the same material, and B is a core layer disposed between the skin layers A; or an A / B / C film structure, wherein A and C are skin layers having different material compositions, and B is a core layer disposed between the skin layers A and C. In two embodiments, the B core layer comprises a formulated resin as described herein. The shrink film can have a skin layer and a core layer in a ratio of 1:2:1, respectively. Each skin layer used in the film of the present invention can independently have a thickness of 8 μm to 30 μm in one embodiment, 10 μm to 25 μm in another embodiment, or 12 μm to 20 μm in another embodiment. The core layer used in the film of the present invention can have, for example, a thickness of 20 μm to 60 μm in one embodiment, 25 μm to 55 μm in another embodiment, or 30 μm to 50 μm in another embodiment. The present invention is not limited to 3 layers and may include more than 3 layers provided that at least one core or inner layer of the multilayer shrink film contains a formulated resin and still allows for the proper balance of properties such as stiffness, toughness and shrinkage.
[0048] Each surface layer of the multilayer shrink film comprises one or more ethylene-based polymer materials, including, for example, HDPE, LDPE, MDPE, LLDPE, and mixtures thereof. In one or more embodiments, the surface layers useful in the present invention may independently comprise HDPE, LDPE, LLDPE, and mixtures thereof. In some embodiments, each surface layer independently comprises LDPE, LLDPE, and HDPE, wherein LDPE has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.2 g / 10 min to 2.0 g / 10 min, LLDPE has a density of 0.915 g / cc to 0.940 g / cc and a melt index I2 of 0.2 g / 10 min to 2.0 g / 10 min, and HDPE has a density of 0.945 g / cc to 0.965 g / cc and a melt index I2 of 0.04 g / 10 min to 1.0 g / 10 min. In other embodiments, each skin layer independently comprises LDPE and LLDPE, wherein the LDPE has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 2.0 g / 10 min, and the LLDPE has a density of 0.915 g / cc to 0.940 g / cc and a melt index I2 of 0.2 g / 10 min to 2.0 g / 10 min.
[0049] In one or more embodiments herein, the shrink film may exhibit one or more of the following properties: a tensile strength of 20 to 40 MPa as measured by ASTM D882; an MD shrinkage of 40 to 70% (alternatively, 45 to 70% or 50 to 70%) and a TD shrinkage of 10 to 50% (alternatively, 12 to 50% or 15 to 50%) as measured by ASTM D2732-03 at 130°C and 20 seconds; a haze of 5 to 50% (alternatively, 5 to 30% or 5 to 20%) as measured by ASTM D1003. In addition to tensile strength, shrinkage, and haze properties, the shrink films described herein may also exhibit an improvement in toughness, which improvement in toughness is quantified in the range of greater than 70 g on Dart Impact (A) (60 micron film) in one embodiment; quantified in the range of greater than 75 g on Dart Impact (A) (60 micron film) in another embodiment; and quantified in the range of greater than 80 g on Dart Impact (A) (60 micron film) in yet another embodiment.
[0050] The monolayer or multilayer shrink films as described herein can be used, for example, in packaging applications. In one or more embodiments, the monolayer or multilayer shrink films described herein are used to package articles.
[0051] Test Method
[0052] density
[0053] Density is measured according to ASTM D792, Method B and is reported in grams per cubic centimeter (g / cc or g / cm3).
[0054] Melt index
[0055] Melt index (MI) or I2 is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, Procedure B, and is reported in grams eluted per 10 minutes (g / 10 min). I10 is measured according to ASTM D 1238, Condition 190°C / 10 kg, Procedure B, and is reported in grams eluted per 10 minutes (g / 10 min).
[0056] Melt Strength
[0057] Melt strength was measured at 200°C using a Goettfert Rheotens 71.97 (Goettfert Inc.; Rock Hill, SC) feeding the melt with a Goettfert Rheotester 2000 capillary rheometer equipped with a flat inlet angle (180 degrees) of 30 mm in length and 2 mm in diameter. The pellets were fed into a barrel (L = 300 mm, diameter = 12 mm), compressed and allowed to melt for 10 minutes, and then extruded at a constant piston speed of 0.2 mm / s, which corresponds to 28.8 s at a given die diameter. -1 The extrudate passes through the Rheotens wheel located 100 mm below the die exit and is sheared by the wheel at 6 mm / s 2 The force applied to the wheel (in N) is recorded as a function of the wheel speed (mm / s). The melt strength is reported as the plateau force (N) before the strand breaks.
[0058] Gel Permeation Chromatography (GPC)
[0059] Chromatographic system is composed of PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with internal IR5 infrared detector (IR5). The automatic sampler oven chamber is set to 160 degrees Celsius, and the column chamber is set to 150 degrees Celsius. The column used is 4 Agilent "Mixed A" 30cm 20 micron linear mixed bed columns and 20um pre-column. The chromatographic solvent used is 1,2,4 trichlorobenzene and contains 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters, and the flow rate is 1.0 ml / min.
[0060] The GPC column set was calibrated with 21 narrow molecular weight distribution polystyrene standards, ranging from 580 to 8,400,000 molecular weights, and arranged in 6 "cocktail" mixtures, with at least ten times the interval between individual molecular weights. Standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, 0.025 g of polystyrene standards were prepared in 50 ml of solvent, and for molecular weights less than 1,000,000, 0.05 g of polystyrene standards were prepared in 50 ml of solvent. The polystyrene standards were dissolved at 80 degrees Celsius and gently stirred for 30 minutes. Equation 1 was used to convert the polystyrene standard peak molecular weight to polyethylene molecular weight (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
[0061] M 聚乙烯 =A×(M 聚苯乙烯 ) B (Equation 1)
[0062] Where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.
[0063] A fifth order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects such that a linear homopolymer polyethylene standard was obtained at 120,000 Mw.
[0064] Plate counts for the GPC column set were performed using decane (prepared as 0.04 g in 50 mL TCB and dissolved for 20 minutes under slow stirring). Plate counts (Equation 2) and symmetry (Equation 3) were measured at 200 microliter injections according to the following equations:
[0065]
[0066] where RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of the peak maximum.
[0067]
[0068] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum position of the peak, tenth height is 1 / 10 the height of the peak maximum, and where post-peak refers to the tail of the peak with a retention volume later than the peak maximum, and where pre-peak refers to the front of the peak with a retention volume earlier than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.
[0069] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml, and the solvent (containing 200 ppm BHT) was added to a septum-covered vial previously sparged with nitrogen by the PolymerChar high temperature autosampler. The samples were dissolved at 160 degrees Celsius for 2 hours under "slow" shaking.
[0070] Based on the GPC results, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer, according to equations 4-6, the PolymerChar GPCOne TMThe software, the baseline-subtracted IR chromatogram at each equally spaced data collection point (i), and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1 were used to determine Mn. (GPC) 、Mw (GPC) and Mz (GPC) Calculation.
[0071]
[0072]
[0073]
[0074] In order to monitor the deviation over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) for each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the alkane peak in the narrow standard calibration (RV (FM calibrated)). It was then assumed that any change in the decane marker peak time was related to a linear change in the flow rate (flow rate (effective)) throughout the run. In order to facilitate the highest accuracy in the RV measurement of the flow marker peak, a least squares fitting procedure was used to fit the peak of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated as Equation 7. By PolymerChar GPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 1% of the nominal flow rate.
[0075] Flow rate (effective) = Flow rate (nominal) * (RV (FM calibration) / RV (FM sample)) (Equation 7)
[0076] Melting and crystallization temperatures and enthalpies
[0077] Melting peak temperature (Tm), crystallization temperature (Tc) and heat of fusion and ΔH crystallization were measured using ASTM D3418 (Standard Test Method for Transition Temperatures and Melting Enthalpy of Polymers and Crystallization by Differential Scanning Calorimetry). A DSC-Q2000 instrument was used and allowed to equilibrate at 0.00°C; and the data memory was placed in the "on" position. A temperature ramp of 10.00°C / min to 200.00°C was first used, and the isothermal was continued for 5.00 minutes. After 5 minutes, the end of cycle 1 was marked. Then, a temperature ramp of 10.00°C / min to 0.00°C was used, and the isothermal was continued for another 5.00 minutes. After 5 minutes, the end of cycle 2 was marked. Another temperature ramp of 10.00°C / min to 200.00°C was used, and the end of cycle 3 was marked, thereby ending the program.
[0078] Tensile properties
[0079] The tensile strength, tensile elongation and secant modulus of the films were measured using ASTM D882.
[0080] Tear
[0081] The tear properties of the films were measured in the machine direction (MD) and transverse direction (TD) using ASTM D1922.
[0082] Falling dart
[0083] The dart drop properties of the films were measured using ASTM D1709, Procedure A.
[0084] 45° gloss
[0085] The 45° gloss properties of the films were measured using ASTM D2457.
[0086] Haze
[0087] The haze characteristics of the films were measured using ASTM D1003.
[0088] puncture
[0089] Membrane penetration was measured using ASTM D5748 by substituting a 0.5 inch diameter stainless steel probe.
[0090] Shrinkage
[0091] The shrinkage properties of the films were measured using ASTM D2732-03.
[0092] transparency
[0093] The clarity properties of a film can be measured using ASTM D1746.
[0094] MD / CD shrinkage force
[0095] The shrinkage force was measured in the longitudinal and transverse directions using an ARES-G2 (TA Instruments). The film was mounted in a torsion fixture and the length was measured by the rheometer measurement mode at a starting temperature of 40°C. The shrinkage of the film was monitored at a constant static strain of 0% with a temperature ramp of 20°C / min from 25°C to 80°C and then from 80°C to 160°C with a temperature ramp of 5°C / min. The shrinkage behavior of the film, including the shrinkage force and the shrinkage temperature, can be monitored.
[0096] Example
[0097] The following examples are provided to further illustrate the present invention in detail but should not be construed as limiting the scope of the claims. Unless otherwise indicated, all parts and percentages are by weight.
[0098] Various terms, names and raw materials used in the present examples (Inv. Ex.) and comparative examples (Comp. Ex.) are explained as follows: Table I describes the raw materials used in the examples.
[0099] Table I - Raw Materials
[0100]
[0101] Notes to Table I:
[0102] *AG-PCR is a LLDPE-based PCR obtained from agricultural film.
[0103] **"HD-PCR" stands for "High-density PCR".
[0104] Film formulation
[0105] Various collation shrink film samples were made using the formulations described in Table II.
[0106] Table II - Formulations of Finishing Shrink Films
[0107]
[0108]
[0109] Examples 1-3 and Comparative Examples A and B were made using the resin formulations for the layers of the collated shrink film described in Table II and using the following general blown film procedure:
[0110] The blown films used in the examples were 60 μm A / B / C three-layer film structures with layer ratios of 1 / 2 / 1 respectively, layers A and C being skin layers and having the same composition as outlined in Table II. The films were blown using a blown film line manufactured by Battenfeld Gloucester. The blown film production line includes the following manufacturing parameters: (1) the three-layer (A / B / C) flat die diameter is 76 mm, the die gap is 2 mm, and the output is about 15 Kg / h; (2) the die temperature distribution: A = 230°C, B = 230°C, and C = 230°C; (3) the blow-up ratio (BUR) is 3.2, the flat fold is 38 cm, and the first traction speed is 6 m / min; (4) the extruder diameter is 32 mm and the L / D ratio is 28; (5) the extruder temperature distribution: A = 200°C / 220°C / 230°C / 230°C / 230°C; B = 200°C / 220°C / 230°C / 230°C / 230°C; and C = 200°C / 220°C / 230°C / 230°C / 230°C; and (6) online split winding.
[0111] The formulated resins used to form the core layer are further analyzed in Tables III-VI.
[0112] Table III - Density and Melt Index of Formulated Resins Used in Core Layers
[0113]
[0114] Table IV - Thermal Characterization of Formulated Resins in the Core Layer
[0115]
[0116]
[0117] Table V - Conventional GPC Results for Formulated Resins in Core Layer
[0118]
[0119] Table VI - Melt Strength of Formulated Resins in the Core Layer
[0120]
[0121] Membrane properties
[0122] Tables VII and VIII describe the mechanical properties of the resulting collation shrink film structures obtained from the examples. As shown in Tables VII and VIII, Inv. Ex. 1-3 have fairly good mechanical properties, which are very important for collation shrink film applications.
[0123] Table VII - Mechanical Properties
[0124]
[0125]
[0126] Table VIII - Mechanical Properties
[0127]
[0128] Table IX describes the optical properties of the collated shrink film structures. When comparing the shrink films of Inv.Ex.1-3 to the shrink film of Comp.Ex.A (no PCR), the optical properties of the shrink films of Inv.Ex.1-3 with PCR are almost at the same level as Comp.Ex.A.
[0129] Table IX - Optical Properties
[0130]
[0131] Table X describes the shrink properties of the resulting shrink film structures obtained from the examples. Inv. Ex. 1-3 show very good shrink properties, even better than Comp. Ex. A and B. Good shrink properties are a very important property for collation shrink film applications.
[0132] Table X - Shrinkage Properties
[0133]
[0134]
[0135] As shown in the above table, the shrink film of the present invention incorporating HDPE post-consumer recycled (PCR) resin exhibits quite good shrink performance while the mechanical and optical properties of the shrink film are not compromised. Therefore, HDPE PCR is suitable for shrink film applications.
Claims
1. A shrink film, comprising: A multilayer film having a core layer and two skin layers; wherein the two skin layers are located on each side of the core layer, respectively, and the core layer comprises a formulated resin, the formulated resin comprising: 20% to 100% by weight of a post-consumer recycled resin derived from recycled high density polyethylene resin; wherein the post-consumer recycled resin has a density of 0.94 g / cc to 0.97 g / cc and a melt index I2 of 0.2 g / 10 min to 1 g / 10 min, and 0 to 60 wt% of a low density polyethylene LDPE and 10 to 60 wt% of a linear low density polyethylene LLDPE, wherein the LDPE has a density of 0.915 to 0.925 g / cc and a melt index I2 of 0.1 to 1 g / 10 min, wherein the LLDPE has a density of 0.915 g / cc to 0.945 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; and Wherein each of the two skin layers comprises one or more ethylene-based polymer materials selected from the group consisting of HDPE, LDPE, MDPE, LLDPE and mixtures thereof.
2. The shrink film of claim 1, wherein the formulated resin comprises 20 to 80 wt% of the post-consumer recycled resin; 0 to 40 wt% of component (i); and 10 to 50 wt% of component (ii).
3. The shrink film according to claim 1 or 2, wherein the film has a thickness of 30 to 120 microns; and / or wherein the formulated resin comprises 35 wt % to 90 wt % of the post-consumer recycled resin; 5 wt % to 30 wt % of component (i); and 25 wt % to 50 wt % of component (ii).
4. The shrink film according to claim 1 or 2, wherein the film has a tensile strength of 20 MPa to 40 MPa as measured by ASTM D882. 5 . The shrink film according to claim 1 , wherein the film has an MD shrinkage of 40% to 70% and a TD shrinkage of 10% to 50% as measured by ASTM D2732-03 at 130° C. and 20 seconds.
6. The shrink film according to claim 1 or 2, wherein the film has a haze of 5% to 50% as measured by ASTM D1003.
7. The shrink film according to claim 1 or 2, wherein the formulated resin is a melt-blended formulated resin.
8. The shrink film of claim 1 or 2, wherein the post-consumer recycled resin is derived from blow molded plastic bottles.
9. The shrink film of claim 1 or 2, wherein the film is a multi-layer collation shrink film having a core layer comprising the formulated resin.
10. An article comprising the shrink film according to any one of claims 1 to 9.
Citation Information
Patent Citations
Film
EP1941998A1
Machine direction oriented film
EP2875948A1
Heat shrinkable, coextruded polyethylene film laminate
US20020187360A1
Collation shrink
US20050064161A1
Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins
US3645992A